Application of Analytic Hierarchy Process-Grey Target Theory Systematic Model in Comprehensive Evaluation of Water Environmental Quality - Wu, Jun; Tian, Xiaogang*; Tang, Ya; Zhao, Yujie; Yandi Hu; Fang, Zili (Water Environment Research, 2010)
Comprehensive evaluation of the water environment for effective water quality management is complicated by a considerable number of factors and uncertainties. It is difficult to combine micro-evaluation with the macro-evaluation process. To effectively eliminate the subjective errors of the traditional analytic hierarchy process (AHP), a new modeling approach—the analytic hierarchy process and grey target theory (AHP-GTT) systematic model—is presented in this study to evaluate water quality in a certain watershed. A case study of applying the AHP-GTT systematic model to the evaluation and analysis of the water environment was conducted in the Yibin section of the Yangtze River, China. The micro-evaluation is based on defining the weights of indices of the water quality (IWQ) of each water cross-section, while the macro-evaluation is based on calculating the comprehensive indices of water environmental quality and analyzing the tendency of the water environment of each cross-section. The results indicated that the Baixi and Shuidongmen sections are seriously polluted areas, with the tendencies of becoming worse. Also, the key IWQs of these two cross-sections are 5-day biochemical oxygen demand and chemical oxygen demand of permanganate, respectively.
Keywords: analytic hierarchy process; evaluation and forecast of water environment; grey target theory; water environmental forecast